Answer:
Step-by-step explanation:
the shape looks like a cube.. and maybe they say something about that outside of the picture, even but assuming that it is a cube, we know all the sides are the same.
we also know that the area of one side of the cube is 3 ![\frac{1}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B4%7D)
so multiply that
W x L = area
3
* 3
= area
10
= area
10.5625 = area
those two answer above are the same .. just one is in fractions and one is in decimals
there are 6 sides on a cube, so multiply the above answer by 6
6* answer = 63.375
63
( this is your answer)
both of those are also identical , but look different for the reasons I mentioned above
use which ever from seems better to you. :)
Answer:
False
Step-by-step explanation:
2x + y = 0
Try (1, -2)
2(1) + (-2) = 0
2 + (-2) = 0
0 = 0
The solution works on the first equation.
-x + 2y = 5
-(1) + 2(-2) = 5
-1 - 4 = 5
-5 = 5
The solution does not work in the second equation.
Answer: False
Answer:
24
Step-by-step explanation:
There are 4 possibilities for the first card.
After that, there are 3 possibilities for the second card.
Finally, there are 2 possibilities for the third card.
The total number of permutations is 4×3×2 = 24.
Here's the list (in alphabetical order):
ARS
ART
ASR
AST
ATR
ATS
RAS
RAT
RSA
RST
RTA
RTS
SAR
SAT
SRA
SRT
STA
STR
TAR
TAS
TRA
TRS
TSA
TSR
Probably the easiest way to do this is to use synthetic division. We already know one of the zeros of the quadratic so we can use that number to find the other zero. If the point is (4, 0), then when y = 0, x = 4. Thus, 4 is a zero. Put 4 outside the "box" and put the coefficients from the quadratic inside, like this: 4 (1 -1 -12). Draw a line and bring down the first one under it. Multiply that 1 by the 4 to get 4. Put that 4 up under the -1 and add to get 3. Multiply 3 by 4 to get 12. Put that 12 up under the -12 and add to get 0. The numbers left under the line are the coefficients for the next polynomial, called the depressed polynomial, and this polyomial is one degree less than the one we started with. Those coefficients are 1 and 3. Therefore, the polynomial is x + 3 = 0. That means that the other zero, or x-intercept, is x = -3.